Istana Kuala Cegar: nostalgic splendour behind a humble facade - Sapian, Abdul Razak; Abdul Majid, Noor Hanita; Abdul Rahim, Zaiton; Denan, Zuraini (IIUM Press, 2013)
This book explains about the historical background of a palace in Alor Setar, Kedah, Malaysia named Istana Kuala Cegar. It reveals its historical development beginning with earlier palaces in Kedah dating from the early 20th century.This palace is an example of unique Art Deco style building which depicts the Western influences as assimilated along with cultural traits by the Royals of Kedah. The book emphasizes on the architectural significance of the building from the history of occupancy to the architectural detail of construction and material.